THU0500 PHYSICAL ACTIVITY AND SCREEN-BASED MEDIA USE IN ADOLESCENTS WITH JUVENILE IDIOPATHIC ARTHRITIS - DATA FROM A GERMAN INCEPTION COHORT. (2nd June 2020) - Milatz, F.; Liedmann, I.; Niewerth, M.; Klotsche, J.; Haas, P.; Dressler, F.; Berendes, R.; Moenkemoeller, K.; Minden, K.
Abstract : Background: Insufficient physical activity (PA) and screen-based media use (SBM) are different aspects of sedentary behavior (SB), independently and inversely related to health and wellbeing. Recent research indicates that adolescents with chronic conditions are at least as likely at risk of being physically inactive or accumulating high levels of screen-based SB when compared with their healthy peers [1]. Objectives: Since PA and SBM have not yet been (sufficiently) evaluated in young patients with juvenile idiopathic arthritis (JIA), our aim was to i) quantify the daily SBM use of adolescents with JIA, ii) measure the frequency of their weekly PA, and iii) compare both aspects of SB with those of age- and sex-matched controls from the general population during the course of the disease. Methods: Data from JIA patients and controls enrolled in the inception cohort study ICON were analyzed. Young people, such as friends and mates, served as the peer group. Patients and peers aged 13 and over were followed prospectively and questioned about their weekly PA frequency and SBM use at a two-year interval. Data from young people for whom at least two questionnaires were available were analyzed using linear mixed models. Results: Data from 209 patients with JIA (63% female, 28% rheumatoid factor negative polyarthritis) and 138 peers (55% female) were included in the analysis. At baseline (T1), 51% of the patients were treated with a DMARD, 58% at follow-up (T2). The proportion of adolescents being physically active at most twice a week was substantially higher in patients than in controls (T1: 59% vs. 43%; T2: 54% vs. 42%). In patients, the total daily screen time was 3.5±2.6 hours at T1 and 3.6±2.5h at T2, respectively. In comparison, a value about 0.5h less was found in the controls both at T1 and T2. Both groups increasingly spent time on mobile phones during the observation period. At T1 (66% vs. 45%) and T2 (60% vs. 45%), the proportion of physically inactive girls was significantly higher than that of boys. Conversely, boys reported higher levels of SBM than girls. Patients with high SBM consumption (>3h/day) showed a significantly lower PedsQLTM psychosocial functioning (OR 0.94; 95%CI: 0.89-0.99) and a significantly higher cJADAS-10 score (OR 1.34; 95%CI: 1.07-1.67) than those who did not exceed the national recommendations on SBM use. Conclusion: Although adolescents with JIA tend to become more physically active during the course of disease, on average they remain more inactive and spend significantly more time on SBM than their peers. Given that high SBM use was associated with lower self-reported psychosocial quality of life and higher disease activity, it is important to develop sustainable and effective interventions to reduce sedentary behaviors in this population. References: [1]Elmesmari R et al. Accelerometer measured levels of moderate-to-vigorous intensity physical activity and sedentary time in children and adolescents with chronic disease: A systematic review and meta-analysis. PLoS One 2017;12:e0179429. Acknowledgments: ICON is supported by a grant from the German Federal Ministry of Education and Research (FKZ 01 ER 1504A) Disclosure of Interests: Florian Milatz: None declared, Ina Liedmann: None declared, Martina Niewerth: None declared, Jens Klotsche: None declared, Peter Haas: None declared, Frank Dressler: None declared, Rainer Berendes: None declared, Kirsten Moenkemoeller: None declared, Kirsten Minden Consultant of: GlaxoSmithKline, Sanofi, Speakers bureau: Roche